Tyrosine phosphorylation of HSC70 and its interaction with RFC mediates methotrexate resistance in murine L1210 leukemia cells. Issue 1 (1st February 2015) - Liu, Tuoen; Singh, Ratan; Rios, Zechary; Bhushan, Alok; Li, Mengxiong; Sheridan, Peter P.; Bearden, Shawn E.; Lai, James C.K.; Agbenowu, Senyo; Cao, Shousong; Daniels, Christopher K.
Highlights: Novelty and impact: Heat shock cognate protein (HSC70) and reduced folate carrier (RFC) colocalizes and interacts with each other in L1210 cells. Tyrosine phosphorylation of HSC70 regulates the transportation of MTX into the cells via the HSC70-RFC system and contributes to MTX resistance in L1210 cells. The studies reveal a novel anti-cancer drug resistant mechanism at molecular levels. Abstract: We previously identified and characterized a 66–68 kDa membrane-associated, tyrosine phosphorylated protein in murine leukemia L1210 cells as HSC70 which is a methotrexate (MTX)-binding protein. In order to further characterize the functional role of HSC70 in regulating MTX resistance in L1210 cells, we first showed that HSC70 colocalizes and interacts with reduced folate carrier (RFC) in L1210 cells by confocal laser scanning microscopy and Duolink in situ proximity ligation assay. The tyrosine phosphorylation status of HSC70 found in the membrane fraction was different from the parental L1210/0 and cisplatin (CDDP)–MTX cross resistant L1210/DDP cells. In MTX-binding assays, HSC70 from L1210/DDP cells showed less affinity for MTX–agarose beads than that of L1210/0 cells. In addition, genistein (a tyrosine phosphorylation inhibitor) significantly enhanced the resistance of L1210/0 cells to MTX. Moreover, site-directed mutation studies indicated the importance of tyrosine phosphorylation of HSC70 in regulating its binding to MTX. These findings suggest that tyrosine phosphorylation of HSC70 regulates the transportation of MTX into the cells via the HSC70–RFC system and contributes to MTX resistance in L1210 cells.